2018
DOI: 10.1002/cjp2.104
|View full text |Cite
|
Sign up to set email alerts
|

Atypical tuberous sclerosis complex presenting as familial renal cell carcinoma with leiomyomatous stroma

Abstract: We report an atypical tuberous sclerosis complex (TSC) phenotype presenting as familial multiple renal cell carcinomas (RCCs) with (angio)leiomyomatous stroma (RCCLS) (5/7 familial RCCs) on a background of multiple angiomyolipomas, hypopigmented skin macules, and absence of neurological anomalies. In the index case and three relatives, germline genetic testing identified a heterozygous TSC2 missense pathogenic variant [c.2714 G > A, (p.Arg905Gln)], a rare TSC‐associated alteration which has previously been ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…An atypical tuberous sclerosis complex phenotype was shown as familial renal cell carcinoma with leiomyomatous stroma. [ 17 ] Ocular coloboma was reported as an atypical ocular lesion in TSC. [ 18 ] These reports indicated that TSC patients may develop atypical symptoms in all organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…An atypical tuberous sclerosis complex phenotype was shown as familial renal cell carcinoma with leiomyomatous stroma. [ 17 ] Ocular coloboma was reported as an atypical ocular lesion in TSC. [ 18 ] These reports indicated that TSC patients may develop atypical symptoms in all organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…The Bosniak classi cation system, created in 1986 [21] , established morphological CT criteria to differentiate between benign cysts and maliganat cysts. Studies have shown that Bosniak criteria combined with ultrasound can greatly improve the diagnostic of benign and malignant renal cystic lesions [22] . If the shape of the renal cyst found by ultrasound examination does not have the characteristics of a simple renal cyst and the boundary with the surrounding renal tissue is unclear, the inner wall is not smooth, or there are nodules and separation, which most likely cystic kidney cancer or a complex renal cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis is sometimes difficult because there are similar imaging features among cystic renal cell carcinoma, conventional renal cell carcinoma with cystic changes and benign renal cystic diseases (17). Cystic small renal carcinoma is generally graded and screened by ultrasound or CT. Bosniak grading is mainly based on examination results of CT.…”
Section: Discussionmentioning
confidence: 99%